Health information exchanges—Unfulfilled promise as a data source for clinical research. (March 2016) - Parker, Carol; Weiner, Michael; Reeves, Mathew
Highlights: Data from HIEs is available and is in limited use by researchers for clinical research. Majority of studies are done to evaluate the use/impact of HIEs on health care delivery/outcomes. Only two studies used HIE data to answer a research objective that was NOT specific to HIE use. Few HIEs are involved in generating published research. Abstract: Objective: To determine the use of health information exchange organizations (HIEs) to support and conduct clinical research. Materials and methods: This scoping review included US-based studies published between January 2003 and March 2014 that used data from an HIE to address at least one of three categories of research: clinical or epidemiological research, financial evaluation, or utilization of health services. Eligibility was not restricted to research on HIEs. Studies with research questions outside of the evaluation of HIEs themselves were sought. Results: Eighteen articles met final study inclusion criteria from an initial list of 847 hits. Fifteen studies addressed a clinical or epidemiological research question, 6 addressed a financial consideration, and 8 addressed a utilization issue. Considerable overlap was found among the research categories: 13 articles addressed more than one category. Of the eighteen included studies, only two used HIE data to answer a research objective that was NOT specific to HIE use. Research designs were varied and ranged from observational studies, such as cohort and cross-sectional studies, to randomized trials. The 18 articles represent the involvement of a small number of HIEs; 7 of the studies were from a single HIE. Discussion: This review demonstrates that HIE-provided information is available and used to answer clinical or epidemiological, financial, or utilization-based research questions; however, the majority of the studies using HIE data are done with the primary goal of evaluating the use and impact of HIEs on health care delivery and outcomes. As HIEs mature and become integrated parts of the health care industry, the authors anticipate that fewer studies will be published that describe or validate the role of HIEs, and more will use HIEs as multi-institutional data sources for conducting clinical research and improving health services and clinical outcomes. Conclusion: Articles identified in this review indicate the limited extent that HIE data are being used for clinical research outside of the evaluation of HIEs themselves, as well as the limited number of specific HIEs that are involved in generating published research. Significant barriers exist that prevent HIEs from developing into an invaluable resource for clinical research including technological infrastructure limitations, business processes limiting secondary use of data, and lack of participating provider support. Research to better understand challenges to developing the necessary infrastructure and policies to foster HIE engagement in research would be valuable as HIEs represent an opportunity to engage non-traditional health care provider research partners.